The Efficiency of Horizontal Sub-Surface Flow Constructed Wetlands with Equisetum Hyemale in Reducing COD and BOD5 in Laundry Wastewater - Christi, Martha Eventina; Suwartha, Nyoman (Syntax Corporation, 2024)
Laundry businesses in Indonesia have high economic development opportunities. However, laundry wastewater in Indonesia does not yet have a good environmental culture and regulations for service users. Constructed wetland can be used as a sustainable biological processing technology, uses low energy, and does not require high costs to process laundry wastewater. The aim of this research is to analyze the ability of horizontal sub-surface flow constructed wetlands in a batch system with different numbers of aquatic bamboo plants (Equisetum hyemale) in degrading chemical oxygen demand (COD) and biochemical oxygen demand (BOD5) in laundry wastewater. The research results showed that reactor 2 HSSF CW with a total of 200 E. hyemale plants produced higher removal efficiency compared to reactor 1 HSSF CW with a total of 120 E. hyemale plants where reactor 2 produced COD and BOD5 removal efficiency respectively. amounted to 88.22% and 90.30% while reactor 1 produced COD and BOD5 removal efficiencies of 86.04% and 88.10% respectively. Based on these results, reactor 1 and reactor 2 horizontal sub-surface flow constructed wetlands with E. hyemale plants produced effective performance in reducing COD and BOD5 concentrations in laundry wastewater.